Investigation of power regimes of Southern Eectrical Networks of 110 kV in case of disconnecting of the high voltage electric transmission line of 400 kV of Moldavian condenced power plant ( MCPP ) – Vulcaneshty - Postolaty V.M.; Bykova E.V. (Problems of the Regional Energetics)
Investigation of power regimes of Southern Eectrical Networks of 110 kV in case of disconnecting of the high voltage electric transmission line of 400 kV of Moldavian condenced power plant ( MCPP ) – Vulcaneshty